The importance of being wicked [large type] - Alexander, Victoria (Center Point Large Print, 2013)
For Winfield Elliott, Viscount Stillwell, finding a prospective bride always seemed easy. Perhaps too easy. With three broken engagements to his name, Win is the subject of endless gossip. His current efforts to hire a company to repair his fire damaged country house seem innocent enough, until the company representative turns out to be a very desirable widow. Lady Miranda Garret expected Win to be flirtatious, even charming. But the awkward truth is that she finds him thoroughly irresistible.